2014
DOI: 10.1074/jbc.m114.597112
|View full text |Cite
|
Sign up to set email alerts
|

A Conserved Three-nucleotide Core Motif Defines Musashi RNA Binding Specificity

Abstract: Background:The Musashi family of RNA-binding proteins promotes progenitor cell proliferation. Results: The majority of Musashi sequence specificity comes from a UAG motif. Sequences outside of UAG make minor contributions to affinity. Conclusion: UAG forms the core Musashi recognition element. Significance: Delineating the sequences that contribute to binding is critical to understanding RNA target selection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
77
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(92 citation statements)
references
References 39 publications
15
77
0
Order By: Relevance
“…In Musashi-targeted genes, RRM1 and RRM2 recognition sequences are found in a close proximity at the 3′-end of the mRNAs (7). MSI1 specifically recognizes motifs (Figure 2B, 3A) variously defined as [(G/A)U(n)AGU (n =1–3)] (3), r(GUAG) and r(UAG) (62), (UAG) (54,63) and other poly-U motifs(55). MSI2 has been suggested to preferentially interact with an ACCUUUUUAGAA′ motif, and other poly-U sequences(37), UAG motifs(63) and UAG containing motifs +/− additional flanking nucleotides(56).…”
Section: Mechanisms Of Post-transcriptional Regulation By Musashi Promentioning
confidence: 99%
See 1 more Smart Citation
“…In Musashi-targeted genes, RRM1 and RRM2 recognition sequences are found in a close proximity at the 3′-end of the mRNAs (7). MSI1 specifically recognizes motifs (Figure 2B, 3A) variously defined as [(G/A)U(n)AGU (n =1–3)] (3), r(GUAG) and r(UAG) (62), (UAG) (54,63) and other poly-U motifs(55). MSI2 has been suggested to preferentially interact with an ACCUUUUUAGAA′ motif, and other poly-U sequences(37), UAG motifs(63) and UAG containing motifs +/− additional flanking nucleotides(56).…”
Section: Mechanisms Of Post-transcriptional Regulation By Musashi Promentioning
confidence: 99%
“…MSI1 specifically recognizes motifs (Figure 2B, 3A) variously defined as [(G/A)U(n)AGU (n =1–3)] (3), r(GUAG) and r(UAG) (62), (UAG) (54,63) and other poly-U motifs(55). MSI2 has been suggested to preferentially interact with an ACCUUUUUAGAA′ motif, and other poly-U sequences(37), UAG motifs(63) and UAG containing motifs +/− additional flanking nucleotides(56). In general, it is thought that both proteins recognize similar sequences and thus likely regulate similar mRNA targets (2,62).…”
Section: Mechanisms Of Post-transcriptional Regulation By Musashi Promentioning
confidence: 99%
“…For many proteins the intrinsic specificity of their individual RBDs appears to be insufficient to accomplish the biologically required binding accuracy for RBPs 3,22,23,104 . Strategies have therefore evolved to enhance the intrinsic specificity of many proteins in order to better discriminate between cognate and non-cognate binding sites.…”
Section: Specific Vs Non-specific Interactionsmentioning
confidence: 99%
“…These findings indicated that Tbx1 could be a direct mRNA target of MSI2. The proposed MSI2‐mRNA binding interactions are further supported by the identification of five multiple Musashi core recognition and binding sequences (UAG) in the Tbx1 3′ UTR (Supplemental Figure S4) (Zearfoss et al, ). To verify this interaction, RNA‐immunoprecipitation (RNA‐IP) was performed using dissociated whole adult mouse testis cells, and indicated significantly enriched Tbx1 mRNA expression (+3.51, p < 0.05) in MSI2‐IP, compared to the control‐IP and sample input, supporting a putative MSI2 protein‐ Tbx1 mRNA interaction (Figure c).…”
Section: Resultsmentioning
confidence: 87%